Implementasi Akad Ijarah Adaptif sebagai Model Pemberdayaan UMKM: Studi Kasus Nurusyubab Market, Cianjur - Faridah Khairun Nisa; Syarifah Gustiawati; Khaidir Fadil (Lembaga Yasin AlSys, 2026)
Although the ijarah contract in leasing practices has been widely examined in Islamic economics literature, studies that specifically investigate adaptive and empowerment-oriented implementations of ijarah for micro, small, and medium enterprises (MSMEs) in community market settings remain limited. This study aimed to analyze the implementation of the ijarah contract in land and building leases and its impact on empowering MSME actors in Nurusyubab Market, Cianjur. A qualitative approach with a field-based case study design was employed, involving ten participants consisting of one mu’jir and nine musta’jir selected purposively. Data were collected through in-depth interviews, observation, and documentation, and were analyzed using the interactive Miles and Huberman model through the stages of data reduction, data display, and conclusion drawing. The findings show that the implementation of ijarah in Nurusyubab Market is not oriented solely toward commercial transactions but is developed as a social empowerment movement grounded in the values of ta’awun and kinship. The predominantly verbal ijarah contracts still fulfill the pillars and conditions of ijarah, with key advantages including flexible ujrah payment without a penalty system, whereby delays are resolved through musyawarah. This scheme has a positive financial impact, with MSME income increasing by 20–50%, and a psychological impact in the form of enhanced feelings of security and peace of mind in doing business. These findings contribute to the development of a humanistic ijarah concept in Islamic economics and broaden understanding of the role of sharia contracts in MSME empowerment, while underscoring the importance of non-exploitative ijarah models and opening avenues for further research in market and other business sectors.